Sentiment Analysis of Indonesian Interest in Korean Food Based on Naïve Bayes Algorithm - Felmi Putra Pratama Subandi; Fauzan Romadlon; Isnaini Nurisusilawati; Anita Chindyana (Jurnal Sosioteknologi, 2022)
Most Korean (South Korean) cultural products, such as drama films, songs, fashion,and food, are rising worldwide. The Korean Wave or Hallyu phenomenon shows howKorean culture is accepted by people all over the world. Social media has piqued theinterest of Indonesians, particularly young people, in Korean culture. The phenomenoncreates new business, especially for Korean food. Many Indonesians are curious totry the food after watching Korean Dramas or Korean artists on social media. Thepurpose of this study is to explore Indonesians’ perspective on Korean food throughsocial media platforms such as Twitter and YouTube. This research measures sentimentanalysis from an Indonesian perspective. The method uses the Naive Bayes algorithmfor data classification. The results show that Korean food has generated positive andnegative interest in Indonesia. It means the opportunity to start a Korean food businessin Indonesia is widely open. As a result, developing a culinary business based on thethriving Korean culture may be a good opportunity.